Profil asam lemak minyak dari jeroan ikan nila dan mas dengan rasio pelarut yang berbeda: Fatty acid profiles of fish oil from tilapia and carp with different solvent ratio - Suseno, Sugeng Heri; Pari, Rizfi Fariz; Ibrahim, Bustami; Ramadhan, Rizki Tri Kurnia; Listiana, Desi; Nurjannah, Farah; Adha, As Syaffa Amalia (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
Extraction of fish oil from the by-products of tilapia and carp can be achieved using an appropriate extraction process. The purpose of this study was to determine the proportion of acetone and fish oil solvents in relation to the oxidation parameters, iodine number, and concentration profile of omega-3 fatty acids present in tilapia and goldfish oil. This study utilized a completely randomized design, in which the treatment ratios of acetone and oil solvent were varied as 3:1, 4:1, 5:1, 6:1, and 7:1 (v/v). The following parameters were examined: the chemical composition, free amino acids, acid value, peroxide value, p-anisidine, total oxidation, iodine value, and fatty acid profile.The omega-3 levels in tilapia and carp were 1.20% and 1.53%, respectively. An Iodine Number Test was employed to identify the most effective solvent treatment, revealing a 5:1 (v/v) ratio as the optimal solution. The increase in the value of omega-3 in tilapia oil amounted to 1.76%, whereas that in carp oil increased from 0.78% to 2.96%, resulting in an average increase of 2.31%.